Longitudinal Investigation of the Stable and Dynamic Components of the World Health Organisation Quality of Life Measure Using Generalisability Theory - Norden, Phoenix April Mary (Auckland University of Technology, 2020)
The abbreviated version of the World Health Organisation Quality of Life questionnaire (WHOQOL-BREF) is a widely used 26-item self-report measure of an individual’s subjective Quality of Life (QOL). However, this scale has not been examined using appropriate methods to distinguish between dynamic (state) and stable (trait) aspects of QOL. Generalisability Theory is the most suitable method to differentiate between state or trait aspects and to evaluate the overall reliability and generalisability of psychometric measurement tools. For the current study we will apply Generalisability theory to the WHOQOL-BREF and its four individual domains as well as the two shorter versions, the WHOQOL-5 and WHOQOL-8. A longitudinal design was used with 130 medical students who completed the 26-item WHOQOL-BREF at three time points. Generalisability theory was applied to estimate state and trait components and to examine potential sources of measurement error within the WHOQOL-BREF. The results from this study provide evaluation of the temporal reliability and generalisability of the WHOQOL-BREF and distinguish between stable and dynamic aspects at the scale, subscales and individual item levels. The results from the study indicate that the WHOQOL-BREF single summary score is the most reliable across time as demonstrated with a generalisability coefficient of 0.90. All four domain subscales and both short versions were found to have less acceptable temporal stability, which was reflected by generalisability coefficients ranging from 0.48 to 0.77 for the domain subscales; and 0.47 and 0.52 for the WHOQOL-5 and WHOQOL-8, respectively. The ability to distinguish to what extent items of each subscale of QOL are measuring state or trait will advance knowledge about which QOL aspects are likely to change in one’s subjective QOL. The results of this study have distinguished between state and trait components of the WHOQOL-BREF at item level. For example, item 18 (How satisfied are you with your capacity for work?) resulted in a state component index (SCI) value of 0.85 indicating that this item is acting in a state-like manner and could potentially be easily influenced by intervention. In contrast, item 15 (How well are you able to get around?) resulted in a SCI value of 0.23, which means that this item is acting in a trait like manner and therefore would be more resistant to change over time. The potential implications of this study include information about areas where target interventions are likely to have the most impact, and which aspects of QOL are likely to undergo relatively minimal change.
Keywords: Quality of Life; Generalisability Theory; Measurement; WHOQOL Research